Privacy and Confidentiality Practices In Adolescent Family Planning Care At Federally Qualified Health Centers. Issue 1 (17th February 2016) - Beeson, Tishra; Mead, Katherine H.; Wood, Susan; Goldberg, Debora Goetz; Shin, Peter; Rosenbaum, Sara
Abstract : CONTEXT: The confidentiality of family planning services remains a high priority to adolescents, but barriers to implementing confidentiality and privacy practices exist in settings designed for teenagers who are medically underserved, including federally qualified health centers (FQHCs). METHODS: A sample of 423 FQHCs surveyed in 2011 provided information on their use of five selected privacy and confidentiality practices, which were examined separately and combined into an index. Regression modeling was used to assess whether various state policies and organizational characteristics were associated with FQHCs' scores on the index. In‐depth case studies of six FQHCs were conducted to provide additional contextual information. RESULTS: Among FQHCs reporting on confidentiality, most reported providing written or verbal information regarding adolescents' rights to confidential care (81%) and limiting access to family planning and medical records to protect adolescents' confidentiality (84%). Far fewer reported maintaining separate medical records for family planning (10%), using a security block on electronic medical records to prevent disclosures (43%) or using separate contact information for communications regarding family planning services (50%). Index scores were higher among FQHCs that received Title X funding than among those that did not (coefficient, 0.70) and among FQHCs with the largest patient volumes than among those with the smallest caseloads (0.43). Case studies highlighted how a lack of guidelines and providers' confusion over relevant laws present a challenge in offering confidential care to adolescents. CONCLUSIONS: The organizational practices used to ensure adolescent family planning confidentiality in FQHCs are varied across organizations.